Isolation and purification of peroxidase enzyme from edible fungus, Calocybe indica - ., Vishaka; Sindhu, Anil; Singh, Pamela; Hooda, Rajni; Singh, Ajay (Mushroom Research, 2019)
Peroxidase enzyme (EC 1.11.1.7) was extracted from Calocybe indica, an edible mushroom, able to grow on a variety of lignocellulosic substrates. The mushroom was cultured on malt extract broth and various parameters like buffer strength, buffer volume, pH and temperature were optimized. The purified enzyme showed maximum activity at pH 5.5 and temp 55°C. The best buffer for enzyme extraction was found to be 0.5M phosphate buffer having pH 5.0. The enzyme action followed the Michelis –Menton Kinetics and gave a Km of 0.7018 mg/ml for guaiacol oxidation over different concentrations (0-10 mg/ml) at pH 5.0 and Vmax was obtained as 0.6948 mg/min.ml using Lineweaver–burk plot. The approximate molecular weight of the purified enzyme after gel filtration was found to be about 67 k Daltons using SAD-PAGE and zymogram method. The final yield of enzyme obtained was 3.4% with purification fold 2.4 and specific activity was 660 µ/mg.